IMPLEMENTASI PENGOSONGAN SUKARELA ATAS GUGATAN PENGOSONGAN TANAH DAN RUMAH DI PENGADILAN NEGERI DENPASAR - I Wayan Sunarta; A.A Sagung Poetri Paraniti; Ida Bagus Anggapura Pidada (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2023)
The resolution of legal disputes in civil matters involves two main pathways: litigation and non-litigation. Voluntary eviction is one form of non-litigation resolution that involves the voluntary change of ownership status of land and houses following an eviction claim. This research explores the implementation of voluntary eviction in the Denpasar District Court, legal perspectives and community practices, changes in ownership status, as well as tax implications and related legal costs. The research methodology used is normative-empirical legal research with a legislative approach and case analysis. The findings indicate that the court plays a crucial role in approving voluntary eviction and providing legal protection. The implementation of voluntary eviction requires preparation, respect for human rights, and the involvement of law enforcement officials if necessary. Changes in ownership status involve administrative procedures, document updates, and tax obligations. It is important to consider the principles of the rule of law theory and the implementation of law in the execution of voluntary eviction